A porous carbon piezoelectric catalyst and its preparation method and application

Through hydrothermal method and high-temperature pyrolysis synthesis, ZIF-8-derived Ca and N co-doped porous carbon catalysts were prepared, which solved the problems of small specific surface area and few active sites of the existing piezoelectric catalysts, achieved efficient piezoelectric catalytic degradation effect, and had good stability and cyclicity.

CN116870942BActive Publication Date: 2025-04-18SHANGHAI UNIVERSITY OF ELECTRIC POWER
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310608129.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-26
Publication Date
2025-04-18
Estimated Expiration
2043-05-26

AI Technical Summary

Technical Problem

The existing piezoelectric catalysts have small specific surface area and few active sites, resulting in limited catalytic performance.

Method used

Through hydrothermal method and high-temperature pyrolysis synthesis, ZIF-8-derived Ca and N co-doped porous carbon catalysts were prepared, retaining the positive dodecahedral structure of ZIF-8, and the specific surface area and active sites of the material were improved by co-doping of Ca and N.

Benefits of technology

The prepared porous carbon piezoelectric catalyst has a high specific surface area and abundant active sites, which significantly improves the piezoelectric catalytic activity, and can effectively degrade rhodamine B, and has good stability and cyclicity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116870942B_ABST
    Figure CN116870942B_ABST
Patent Text Reader

Abstract

The invention discloses a porous carbon piezoelectric catalyst and its preparation method and application, including dissolving zinc nitrate hexahydrate and calcium chloride in methanol at the same time to form liquid A; dissolving 2-methylimidazole in methanol, mixing evenly to obtain liquid B; rapidly adding liquid A to liquid B, stirring evenly to obtain suspension C; moving suspension C to a reactor for hydrothermal reaction to obtain a reaction product; centrifuging, washing and drying the obtained reaction product to obtain Ca / ZIF-8 nanoparticles; placing Ca / ZIF-8 in a tubular furnace, calcining the obtained black solid powder under an inert gas atmosphere; washing the black solid powder with an acid solution and deionized water respectively, and vacuum drying to obtain Ca, N co-doped porous carbon. The present invention introduces calcium and nitrogen atoms of different electronegativity to cause the redistribution of the charge density of the carbon skeleton, significantly improving the piezoelectric catalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of catalytic materials and piezoelectric catalysis, and specifically relates to a porous carbon piezoelectric catalyst and a preparation method and application thereof. Background Art

[0002] At present, various environmental pollutants continue to accumulate in water, air and soil, threatening the earth's ecological environment, and environmental remediation has become an imminent issue. Among various environmental remediation technologies, piezoelectric catalysis technology has attracted much attention because of its unique use of the piezoelectric effect. Piezoelectric catalysis can provide a new strategy for the reuse of waste mechanical energy by collecting tiny waste water and wind energy in nature. Compared with traditional catalysis, piezoelectric catalysis has many advantages, such as no need for additional electrical energy, light-free operability, and the use of low-frequency mechanical energy. Most piezoelectric materials can generate a built-in electric field due to their own piezoelectric effect, which promotes the separation of electrons and holes.

[0003] Electron and hole pairs can trigger redox reactions to produce active oxygen species, that is, the piezoelectric effect can directly degrade pollutants. Therefore, the research and development of high-activity and low-cost piezoelectric catalysts is one of the important areas for future environmental applications.

[0004] However, most reported piezoelectric catalysts have small specific surface areas and fewer active sites, resulting in limited piezoelectric catalytic performance.

[0005] Carbon-based nanomaterials have been widely used in various fields due to their high specific surface area, low cost and ease of preparation. However, carbon materials are rarely used as piezoelectric catalysts due to the lack of structural polarization. Nitrogen-doped carbon-based materials, especially graphene-related materials and carbon nanotubes, show piezoelectric activity related to asymmetric distribution of electrons under mechanical strain, but there are no reports on porous carbon nanoparticle piezoelectric catalytic materials and piezoelectric catalytic performance. Summary of the invention

[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a porous carbon piezoelectric catalyst.

[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a porous carbon piezoelectric catalyst, comprising:

[0010] Dissolve zinc nitrate hexahydrate and calcium chloride in methanol simultaneously to form liquid A;

[0011] Dissolve 2-methylimidazole in methanol and mix well to obtain solution B;

[0012] Rapidly add liquid A into liquid B and stir evenly to obtain suspension C;

[0013] The suspension C is transferred to a reactor for hydrothermal reaction to obtain a reaction product;

[0014] The obtained reaction product is centrifuged, washed, and dried to obtain Ca / ZIF-8 nanoparticles;

[0015] The Ca / ZIF-8 was placed in a tube furnace and calcined under an inert gas atmosphere to obtain a black solid powder;

[0016] The black solid powder was washed with an acid solution and deionized water respectively to remove the residual Zn-containing species and unstable calcium, and then vacuum dried to obtain Ca and N co-doped porous carbon.

[0017] As a preferred embodiment of the preparation method of the present invention, the zinc nitrate hexahydrate and calcium chloride are dissolved in methanol at the same time, wherein the molar ratio of zinc nitrate hexahydrate to calcium chloride is 1-3:1, and the ratio of zinc nitrate hexahydrate to methanol is 1-3 mmol:7.5 mL.

[0018] As a preferred embodiment of the preparation method of the present invention, the 2-methylimidazole is dissolved in methanol, wherein the ratio of 2-methylimidazole to methanol is 8 mmol:15 mL.

[0019] As a preferred embodiment of the preparation method of the present invention, wherein: liquid A is quickly added to liquid B, wherein the molar ratio of 2-methylimidazole to zinc nitrate hexahydrate is 8:1-3.

[0020] As a preferred embodiment of the preparation method of the present invention, the hydrothermal reaction has a reaction temperature of 110 to 140° C. and a reaction time of 3 to 6 hours.

[0021] As a preferred embodiment of the preparation method of the present invention, the reaction product is centrifuged, washed and dried, wherein the washing is performed with methanol and the drying is performed with vacuum heating, the temperature of the vacuum heating drying is 50 to 80°C and the time is 5 to 24 hours.

[0022] As a preferred embodiment of the preparation method of the present invention, the inert gas comprises one of nitrogen, argon and helium;

[0023] The calcination includes heating to 800-1000° C. at a heating rate of 5-10° C. / min in an inert gas atmosphere and maintaining the temperature for another 2-4 hours.

[0024] As a preferred embodiment of the preparation method of the present invention, the acid solution comprises a 2-4M hydrochloric acid solution.

[0025] Another object of the present invention is to overcome the deficiencies in the prior art and provide a porous carbon piezoelectric catalyst prepared by a method for preparing a porous carbon piezoelectric catalyst, wherein the catalyst has a pore size of 1.5 to 3.0 nm and a specific surface area of ​​800 to 1000 m 2 / g, and the calcium loading is 0.1-1wt%.

[0026] Another object of the present invention is to overcome the deficiencies in the prior art and to provide a method for preparing a porous carbon piezoelectric catalyst and to use the porous carbon piezoelectric catalyst prepared in the degradation of Rhodamine B in polluted wastewater.

[0027] Beneficial effects of the present invention:

[0028] (1) The present invention provides a method for preparing a porous carbon piezoelectric catalyst, which uses ZIF-8 as a template and retains the regular dodecahedral structure of ZIF-8. The porous carbon piezoelectric catalyst has high hydrothermal stability and a large specific surface area (800-1000 m 2 / g); the introduction of calcium and nitrogen atoms with different electronegativity leads to the redistribution of the charge density of the carbon skeleton, which destroys the local lattice symmetry of the porous carbon and significantly improves the piezoelectric catalytic activity.

[0029] (2) The Ca and N co-doped porous carbon catalyst synthesized by the hydrothermal method and high-temperature pyrolysis in the present invention can not only effectively piezoelectrically catalytically degrade rhodamine B, but also maintain high stability. Calcium (Ca) is the fifth most abundant element in the earth's crust, which is more economical and environmentally friendly.

[0030] (3) The preparation process and equipment of the present invention are simple, have good repeatability, and have good industrial application prospects. The method uses a metal organic framework as a carrier to load the alkaline earth metal calcium element, drives the Ca atomic-level dispersed loading under the protection of an inert gas at 900°C, and enables the catalyst to have high stability and catalytic performance at a low loading amount (0.3wt%).

[0031] (4) The present invention provides a ZIF-8 derived Ca, N co-doped porous carbon piezoelectric catalyst and a preparation method thereof, which can achieve the purpose of catalytic degradation of Rhodamine B by ultrasonic treatment without the need for light. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0033] Figure 1 is a scanning electron microscope image of Ca-NC of Example 1 of the present invention;

[0034] Figure 2 is a high-resolution transmission electron microscopy image of Ca-NC of Example 1 of the present invention;

[0035] Figure 3 is the X-ray diffraction spectrum of Ca-NC of Example 1 and NC of Comparative Example 3 in the present invention;

[0036] Figure 4 is the Raman image of the Ca-NC of Example 1 and the NC of Comparative Example 3 in the present invention;

[0037] Figure 5 It is the N2 adsorption-desorption and pore size distribution diagram of the Ca-NC of Example 1 and the NC of Comparative Example 3 in the present invention;

[0038] Figure 6 is an X-ray photoelectron spectrum of Ca-NC of Example 1 of the present invention;

[0039] Figure 7 is a transient piezoelectric current response diagram of the Ca-NC of Example 1 of the present invention and the NC of Comparative Example 3;

[0040] Figure 8 It is a diagram of the piezoelectric catalytic degradation efficiency of rhodamine B by Ca-NC of Example 1 of the present invention and Ca / ZIF-8, ZIF-8, and NC of Comparative Examples 1-3;

[0041] Fig. 9 is a graph showing the efficiency of Ca-NC in Example 1 of the present invention in degrading different concentrations of Rhodamine B;

[0042] Fig.10 This is a diagram showing the reuse effect of Ca-NC piezoelectric catalytic degradation of Rhodamine B in Example 1 of the present invention. DETAILED DESCRIPTION

[0043] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0044] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0045] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0046] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.

[0047] Example 1

[0048] A method for preparing a ZIF-8 derived Ca, N co-doped porous carbon piezoelectric catalyst, the specific steps are as follows:

[0049] (1) 2.0 mmol of Zn(NO3)2·6H2O and 1.0 mmol of CaCl2 were simultaneously dissolved in 7.5 ml of methanol to form a clear solution A;

[0050] 8.0 mmol of 2-methylimidazole was dissolved in 15 ml of methanol to form solution B;

[0051] After A and B were mixed evenly, they were stirred vigorously for 5 min to form a suspension, which was transferred to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave, and the sealed container was heated at 120 °C for 4 h and then cooled to room temperature;

[0052] Ca / ZIF-8 was obtained by centrifugation at 8000 rpm, washing with methanol four times and drying in a vacuum oven.

[0053] (2) Ca / ZIF-8 was placed in a tube furnace and heated to 900°C at a heating rate of 5°C / min under an argon (50 mL / min) atmosphere and maintained at this temperature for another 3 h to obtain a black solid powder;

[0054] The black solid powder was then acid-washed with 3M HCl for 2 h to remove zinc species and unstable calcium in the framework;

[0055] The final sample was centrifuged and washed alternately with ethanol and distilled water for 3 times each, and dried in a vacuum oven at 60 °C to obtain the Ca-NC catalyst.

[0056] The Ca-NC prepared in Example 1 was tested by scanning electron microscopy and high-resolution transmission electron microscopy. Figure 1 and Figure 2 .

[0057] Figure 1 is a schematic diagram of a scanning electron microscope of Ca-NC in Example 1 of the present invention, Figure 2 Schematic diagram of high-resolution transmission electron microscopy of Ca-NC in Example 1 of the present invention. Figure 1 As shown in the figure, it can be clearly seen that Ca-NC presents a standard regular dodecahedron structure, indicating that high temperature treatment does not affect the structure of the material, proving the high temperature stability of Ca-NC materials. Figure 2 As shown, the high-resolution transmission electron microscopy image shows no obvious lattice fringes, indicating that Ca-NC is mainly composed of an amorphous structure, proving the effect of acid washing.

[0058] The Ca-NC prepared in Example 1 was characterized by X-ray photoelectron spectroscopy. Figure 6 .like Figure 6 As shown, the full energy spectrum of Ca-NC prepared in Example 1 shows that we have successfully prepared a material containing the four elements of C, N, O, and Ca.

[0059] Comparative Example 1

[0060] Ca / ZIF-8 was obtained in the same manner as in Example 1 (1).

[0061] Comparative Example 2

[0062] 2.0 mmol of zinc nitrate hexahydrate was dissolved in 7.5 mL of methanol, which was called solution A.

[0063] 8.0 mmol of 2-methylimidazole was dissolved in 15 mL of methanol, which was designated as solution B.

[0064] After solution A and solution B were completely dissolved, solution A was quickly mixed with solution B for 5 minutes under vigorous stirring to form a uniform suspension. The suspension was then transferred to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave, placed in an oven, heated to 120°C, and maintained at this temperature for 4 hours.

[0065] Then, the autoclave was cooled to room temperature. After centrifugation at 8000 rpm for 5 minutes, the solution was then redispersed in ethanol and centrifuged to collect the particles. This process was repeated four times.

[0066] Finally, the resultant was dried in a vacuum oven at 60 °C to obtain ZIF-8 nanoparticles.

[0067] Comparative Example 3

[0068] (1) ZIF-8 was obtained in the same manner as in Comparative Example 2.

[0069] (2) The ZIF-8 nanoparticles were placed in a tube furnace, heated to 900 °C at a heating rate of 5 °C / min under an argon (50 mL / min) atmosphere, and maintained at this temperature for another 3 h to obtain a black solid powder.

[0070] The black solid powder was then acid washed with 3 M HCl for 2 h to remove the zinc species in the framework.

[0071] The final sample was centrifuged and washed alternately with ethanol and distilled water 3 times each, and dried in a vacuum oven at 60 °C to obtain the NC catalyst.

[0072] X-ray diffraction analysis and Raman analysis were performed on the Ca-NC prepared in Example 1 and the NC prepared in Comparative Example 3. The test results are shown in Figure 3 and Figure 4 .

[0073] like Figure 3 As shown in FIG. 1 , the Ca-NC prepared in Example 1 and the NC prepared in Comparative Example 3 show characteristic peaks of carbon at around 25° and 44°, corresponding to (002) and (101) diffracted carbon, respectively. The XRD spectrum of Ca-NC only diffracts graphite carbon, and no other diffractions are detected, which is consistent with the Figure 2 The results are consistent. Figure 4 As shown, the ID / IG value of Ca / NC is 1.21, which is higher than the ID / IG value of NC (1.15), indicating that the implantation of Ca atoms leads to more structural defects in the carbon matrix.

[0074] The Ca-NC prepared in Example 1 and the NC prepared in Comparative Example 3 were subjected to N2 adsorption-desorption and pore size distribution tests. The test results are shown in Figure 5 .like Figure 5 As shown in Figure 1, the specific surface area of ​​Ca-NC prepared in Example 1 is 921.2 m 2 / g, total pore volume 0.54cm 3 / g, while the specific surface area of ​​NC prepared in Comparative Example 3 is 810.6m 2 / g, total pore volume 0.43cm 3 The larger specific surface area and total pore volume of Ca-NC are beneficial to the effective mechanical capture and rapid transfer of charge carriers and adsorption of organic dyes, which in turn facilitates the degradation of organic dyes.

[0075] The Ca-NC prepared in Example 1 and the NC prepared in Comparative Example 3 were tested for transient piezoelectric current response. Figure 7 .like Figure 7As shown in the figure, under non-vibration conditions, the Ca-NC prepared in Example 1 and the NC electrode prepared in Comparative Example 3 have no current output. After turning on ultrasound, the output current of Ca-NC rapidly increases to 40 μA, which is higher than the output current of NC. This indicates that the addition of single-atom calcium enhances the mobility of carriers.

[0076] Comparative Example 4

[0077] The Ca-NC prepared in Example 1 and the ZIF-8, Ca / ZIF-8 and NC prepared in Comparative Examples 1-3 were used as catalysts to piezoelectrically degrade rhodamine B.

[0078] The specific experimental process of the Rhodamine B degradation experiment is as follows:

[0079] Generally, 30 mg of Ca-NC prepared in Example 1 and ZIF-8, Ca / ZIF-8 and NC prepared in Comparative Examples 1-3 were dispersed in 30 mL of RhB solution (5 mg / L) as catalysts.

[0080] Afterwards, the suspension was stirred at 400 rpm for 60 min in the dark to achieve complete adsorption–desorption equilibrium between the catalyst particles and RhB molecules.

[0081] The mixed solution was then placed in an ultrasonic generator (120 W, 40 kHz), and about 3 mL of the suspension was collected every 30 minutes and centrifuged (8000 rpm, 3 min) to remove the catalyst particles.

[0082] The results were measured by UV-visible spectrophotometer. Figure 8 .

[0083] Figure 8 It is the influence of different types of catalysts in the present invention on the removal effect of Rhodamine B. Among them, the horizontal axis represents the degradation reaction time, in minutes, and the vertical axis represents the concentration ratio (i.e., the concentration of Rhodamine B in the solution / the initial concentration of Rhodamine B).

[0084] from Figure 8It can be seen that after the addition of Ca-NC, the catalytic performance is significant, with a degradation rate of about 100% within 150 minutes, and the degradation effect is the best. NC is second, with a degradation rate of 74.5%. ZIF-8 and Ca / ZIF-8 have the slowest degradation, degrading 34% and 34.2% of RhB within 150 minutes, respectively. When single-atom Ca / NC catalysts are used, RhB is almost completely degraded within 150 minutes, indicating that this excellent catalytic performance may be attributed to the contribution of NC and the active sites of single-atom Ca. Therefore, the enhancement of Rhodamine B degradation in Ca-NC further demonstrates the important role of the introduction of Ca / N co-doping. The formation of Ca-N bonds in porous carbon materials has been shown to regulate the electronic structure of carbon-based materials, further improving the piezoelectric catalytic degradation of RhB.

[0085] Comparative Example 5

[0086] The Ca-NC prepared in Example 1 was used to degrade Rhodamine B at different concentrations. The specific experimental process of the Rhodamine B degradation experiment is as follows:

[0087] Typically, 30 mg of the catalyst was dispersed in 30 mL of RhB solution (5 mg / L, 10 mg / L, 30 mg / L). Afterwards, the suspension was stirred at 400 rpm in the dark for 60 minutes to achieve complete adsorption-desorption equilibrium between the catalyst particles and the RhB molecules. The mixture was then placed in an ultrasonic generator (120 W, 40 kHz), and about 3 mL of the suspension was collected every 30 minutes and centrifuged (8000 rpm, 3 min) to remove the catalyst particles. The results were measured using a UV-visible spectrophotometer. Fig. 9 .

[0088] Fig. 9 It is the effect of Ca-NC prepared in Example 1 of the present invention on the removal effect of different concentrations of Rhodamine B. Among them, the horizontal axis represents the degradation reaction time, the unit is minute, and the vertical axis represents the concentration ratio (i.e. the concentration of Rhodamine B in the solution / the initial concentration of Rhodamine B).

[0089] from Fig. 9 It can be seen that when the concentration of Rhodamine B is 5 mg / L, the removal rate of Rhodamine B is about 100% within 150 minutes. Then, as the concentration of Rhodamine B increases, the removal rate of Rhodamine B decreases. This is because for a specific catalyst dosage, the number of active sites is constant, and the increase in Rhodamine B concentration may exceed the number of active sites.

[0090] When a large number of dye molecules are present in the aqueous solution, the reaction sites may be covered by these molecules, resulting in a reduction in the active components.

[0091] Comparative Example 6

[0092] The cyclic performance experiment of Ca-NC in Example 1 for degradation of Rhodamine B was conducted by using Ca-NC in Example 1 as a catalyst and performing 4 cyclic experiments.

[0093] The devices and test instruments used in the experiment are the same as those in Application Example 1. The specific experimental process is as follows:

[0094] Take 30 mg of the Ca-NC material in Example 1 and disperse it in 30 mL of a 5 mg / L RhB solution. Afterwards, stir the suspension at 400 rpm in the dark for 60 minutes to achieve complete adsorption-desorption equilibrium between the catalyst particles and the RhB molecules. Then place the mixed solution in an ultrasonic generator (120 W, 40 kHz), collect about 3 mL of the suspension every 30 minutes and centrifuge (8000 rpm, 3 min) to remove the catalyst particles. Measured using a UV-visible photometer. After the experiment, the catalyst was recovered by centrifugation, washing, and drying. In the second cycle, the completely dried sample was subjected to the experimental conditions of the first cycle again, and the cycle was repeated until the fourth cycle was completed. See the results. Fig.10 .

[0095] Depend on Fig.10 It can be seen that after 10 cycle experiments, the Ca-NC prepared in Example 1 still has good catalytic degradation performance, indicating that Ca-NC has good cyclability.

[0096] The present invention provides a method for preparing and applying a ZIF-8 derived Ca, N co-doped porous carbon piezoelectric catalyst. The material is synthesized in two steps by a hydrothermal method and a high-temperature carbonization, and the Ca atoms are successfully anchored on the N-doped porous carbon to prepare a Ca-NC piezoelectric catalyst with a high specific surface area and abundant active sites.

[0097] Under ultrasonic vibration, the cavitation effect produces high-frequency mechanical impact on Ca-NC. The incorporation of single-atom calcium destroys the symmetry of the local lattice of the carbon substrate material, causing changes in its chemical state and carrier distribution, triggering the generation of piezoelectric potential in the crystal. After separation, the intrinsic free carriers migrate to the surface of Ca-NC driven by the polarization electric field, triggering redox reactions and degrading rhodamine B. The abundant structural defects and Ca-N active sites in Ca-NC effectively achieve high-voltage electrocatalytic degradation of rhodamine B.

[0098] Therefore, the present invention synthesizes a ZIF-8 derived Ca, N co-doped porous carbon piezoelectric catalyst through the embodiment, which has a high degradation rate and good recyclability for rhodamine B. For example, when Ca-NC is used to degrade rhodamine B for 150 minutes, the degradation rate reaches about 100%; Ca-NC still has a good degradation effect on rhodamine B of different concentrations; it can still achieve a good catalytic effect after being recycled for 4 times.

[0099] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for preparing a porous carbon piezoelectric catalyst, characterized in that: include, Dissolve zinc nitrate hexahydrate and calcium chloride in methanol at the same time to form liquid A, wherein the molar ratio of zinc nitrate hexahydrate to calcium chloride is 1-3:1, and the ratio of zinc nitrate hexahydrate to methanol is 1-3 mmol:7.5 mL; Dissolve 2-methylimidazole in methanol and mix well to obtain solution B, wherein the ratio of 2-methylimidazole to methanol is 8 mmol:15 mL; Liquid A is quickly added to liquid B and stirred evenly to obtain suspension C, wherein the molar ratio of 2-methylimidazole to zinc nitrate hexahydrate is 8:1-3; The suspension C is transferred to a reactor for hydrothermal reaction to obtain a reaction product; The obtained reaction product is centrifuged, washed, and dried to obtain Ca / ZIF-8 nanoparticles; The Ca / ZIF-8 is placed in a tube furnace and calcined under an inert atmosphere to obtain a black solid powder, wherein the inert atmosphere is one of nitrogen, argon and helium, and the calcination is performed by heating the mixture to 800-1000° C. at a heating rate of 5-10° C. / min under the inert atmosphere and maintaining the mixture at the temperature for another 2-4 hours; The black solid powder is washed with an acid solution and deionized water respectively to remove residual Zn-containing species and unstable calcium, and then vacuum dried to obtain Ca and N co-doped porous carbon, wherein the acid solution includes a 2-4M hydrochloric acid solution.

2. The preparation method according to claim 1, characterized in that: The hydrothermal reaction has a reaction temperature of 110 to 140° C. and a reaction time of 3 to 6 hours.

3. The preparation method according to claim 1, characterized in that: The obtained reaction product is centrifuged, washed and dried, wherein the washing is performed with methanol and the drying is performed by vacuum heating drying, the vacuum heating drying temperature is 50 to 80° C., and the drying time is 5 to 24 hours.

4. The porous carbon piezoelectric catalyst prepared by the preparation method according to any one of claims 1 to 3, characterized in that: The catalyst has a pore size of 1.5 to 3.0 nm and a specific surface area of ​​800 to 1000 m 2 / g, and the calcium loading is 0.1-1wt%.

5. Use of the porous carbon piezoelectric catalyst according to claim 4 in degrading Rhodamine B in polluted wastewater.